Factors influencing entrepreneurial intention among undergraduate students in Indonesia - Sukmawati, Alya Rizkiarini (2021)
Entrepreneurial interest is a strategic determinant of a person's desire to start and run a successful business. Entrepreneurial intention is characterised as a person's increasing a state of consciousness that they want to create a new business or build new core value in their current organisation. The purpose of this research is to examine the relationship between entrepreneurship education, family environment, self-concept, subjective norms, perceived behavioral control on entrepreneurial intention among undergraduate students. In precise, entrepreneurship education, family environment, self-concept, subjective norms, and perceived behavioral control were used as the measurement tool to analyse the relationship and impact on entrepreneurial intention. The data for this research was collected through survey method with 31 items of questionnaire. Total of 371 respondents included in this research was randomly selected using simple random sampling technique among undergraduates students in Indonesia. This study used SPSS version 27.0 to analyse the data. The result of this study can be used by university or other to perform better in relation. The findings extend the researcher understanding of predictor such as entrepreneurship education, self-concept, and perceived behavioral corntrol that influence entrepreneurial intention among undergraduates students in Indonesia.